Integrative Monitoring System for Arabic Learning Plans in University-Affiliated Islamic Boarding Schools - Kafi, Fina Aunul (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2023)
Universities often face challenges in ensuring the quality of education, especially in the learning segment during the lecture process. Therefore, this study examines the phenomenon of quality and quantity, which is the basis for the quality of Arabic learning planning at Al-Falah As-Sunniyyah Jember University. The main objective of this study is to identify and explore effective strategies for ensuring the quality and quantity of education through an integrative monitoring system for Arabic language learning planning. Using a qualitative approach and literature studies as methods, the writer collected data by searching related literature. The data were analyzed using qualitative methods involving reading, synthesizing, and interpreting information found in the literature. Research findings confirm that the implementation of an integrative monitoring system appropriately has great potential to be used as the best model in planning Arabic language learning to improve the quality of learning significantly.